Customers' product choices and dealers' decision to carry Faiza's product and its relationship with product attributes (in Central and Southern of Peninsular Malaysia) / Noorezati Md Noksen - Md Noksen, Noorezati (Faculty of Business and Management, 2004)
Recently, many companies involved in spices industries whereby companies try to introduce formulated spices with different recipe. FAIZA MARKETING is one of the company that marketed formulates spices, while introduce new formulated recipe to target segment. Company try to penetrate leader market which offer similar product. In the consumer perception, products that offer a good quality and fulfil their needs in term of taste can create more demand. In other words, consumers are very particular about intangible product offer other than tangible product. So that, company try to cater target segment with emphasis on product attribute that effect a choice brand of formulated spices.